Obstetric Intraoperative Cell Salvage: A Review of an Established Cell Salvage Service With 1170 Reinfused Cases. Issue 2 (June 2020) - Sullivan, I.J.; Ralph, C.J.
Abstract : ( Anaesthesia . 2019;74:976–983) Over the last 20 years, obstetric hemorrhage has remained a dominant cause of maternal death; this trend shows no sign of changing in the near future. A standard treatment for obstetric hemorrhage is allogeneic (donor) blood transfusion, but autologous (cell salvaged) blood transfusion is becoming a more viable alternative to allogeneic blood transfusion. On the basis of a recent multicenter randomized trial that concluded the routine use of cell salvage during cesarean section was not cost-effective, updated guidelines from the Association of Anaesthetists no longer recommend routine cell salvage during cesarean section. They do encourage autologous blood transfusion when significant blood loss is expected. The authors of this article reported on their use of cell salvage during cesarean section and based on their results argued that cell salvage can be a safe and economically feasible option for patients undergoing cesarean section.